A Comparative Analysis of Toxicology and Non-Toxicology Care in Intoxicated Patients with Acute Kidney Injury - Chi-Syuan Pan; Chun-Hung Chen; Wei-Kung Chen; Han-Wei Mu; Kai-Wei Yang; Jiun-Hao Yu (Medicina)
Background and Objectives: Intoxicated patients with acute kidney injury (AKI) experience high morbidity and mortality. While prior studies suggest that toxicology care settings improve outcomes, the impact of care settings on patients with AKI remains unclear. This study aimed to compare the outcomes of intoxicated patients with AKI managed in toxicology versus non-toxicology care settings. Materials and Methods: This retrospective cohort study included intoxicated patients admitted to a tertiary hospital between January 2022 and December 2023. Patients were categorized into toxicology and non-toxicology care settings. Demographic characteristics, clinical outcomes focusing on mortality and length of hospital stay, and evaluation scores were compared. Results: A total of 31 intoxicated patients with AKI were included in the study. There were no significant differences in mortality or hospital length of stay between toxicology and non-toxicology care settings. However, the mortality rate in the AKI group was significantly higher (16%) compared to intoxicated patients without AKI (1.9%). Additionally, hospital stays were consistently longer in the AKI group than in the non-AKI group across all age groups. Conclusions: Hospital length of stay and mortality did not differ significantly between toxicology and non-toxicology care settings for intoxicated patients with AKI. However, both hospital length of stay and mortality were notably higher in patients with AKI compared to those without AKI.